The Effect of Discovery Learning with Powtoon and Word-wall on the Interest and Learning Outcomes on XI MIPA Students - Irham Irham; Army Auliah; Ahmad Fudhail Majid (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
This research is a quasi-experiment which aims to investigate the effect of the Discovery Learning Model supported by Powtoon Media and Word-wall Game on the interest and learning outcomes of class XI MIPA SMAN 9 Makassar students in learning chemical bonds. The independent variable is the use of the Discovery Learning Model with Powtoon and Word-wall Game media, while the dependent variable is student interest and learning outcomes. The research population consisted of students from class XI MIPA SMAN 9 Makassar, with a sample consisting of class XI MIPA 1 as the experimental group and class XI MIPA 2 as the control group. Data analysis uses descriptive and inferential statistics. The results show that the average learning interest and learning outcomes of the experimental group are significantly higher than the control group. Hypothesis testing using the Mann Whitney test confirmed significant differences between the two groups in learning interest and learning outcomes. These findings show that the Discovery Learning Model supported by Powtoon Media and Word-wall Game has a positive influence on the interest and learning outcomes of class XI MIPA students at SMAN 9 Makassar in chemical bonding material.